The Essential Oil Compositions of Ocimum basilicum from Three Different Regions: Nepal, Tajikistan, and Yemen. Issue 2 (16th February 2016) - Sharopov, Farukh S.; Satyal, Prabodh; Ali, Nasser A. Awadh; Pokharel, Suraj; Zhang, Hanjing; Wink, Michael; Kukaniev, Muhammadsho A.; Setzer, William N.
Abstract: The aerial parts of Ocimum basilicum L. were collected from four different geographical locations, Sindhuli and Biratnagar (Nepal), Chormaghzak village (Tajikistan), and Sana'a (Yemen). The essential oils were obtained by hydrodistillation and analyzed by gas chromatography/mass spectrometry. A cluster analysis of 179 essential oil compositions revealed six major chemotypes: Linalool, eugenol, estragole, methyl eugenol, 1, 8‐cineole, and geraniol. All four of the basil oils in this study were of the linalool‐rich variety. Some of the basil oils were screened for bioactivity including antimicrobial, cytotoxicity in human cancer cells, brine shrimp lethality, nematicidal, larvicidal, insecticidal, and antioxidant. The basil oils in this study were not notably antibacterial, cytotoxic, antioxidant, nor nematicidal, but were active in the brine shrimp lethality test, and did show larvicidal and insecticidal activities. Abstract :